MR lung perfusion measurements in adolescents after congenital diaphragmatic hernia: correlation with spirometric lung function tests - Bischof, Verena; Zahn, Katrin; Maurer, Kristina; Wessel, Lucas; Schaible, Thomas; Schönberg, Stefan; Weiß, Christel; Zöllner, Frank G.; Weis, Meike (European radiology, 2022)
To evaluate whether lung perfusion continues to be reduced in 10-year-old children after congenital diaphragmatic hernia (CDH) and whether lung perfusion values correlate with spirometric lung function measurements.
Gesehen am 08.08.2023